2018
DOI: 10.1371/journal.pone.0201048
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness in children: Evidence for criterion-referenced cut-points

Abstract: IntroductionCriterion-referenced cut-points for field-based cardiorespiratory fitness for children (CRF) are lacking. This study determined: (a) the association between CRF and obesity, (b) the optimal cut-points for low CRF associated with obesity in children, and (c) the association between obesity and peak oxygen uptake () estimated from the 20-m shuttle run test using two different prediction equations.MethodsA total of 8,740 children aged 10.1±1.2 were recruited from 11 sites across Canada. CRF was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 39 publications
(90 reference statements)
5
37
0
2
Order By: Relevance
“…Our study extended the results of a recent study in 8740 Canadian children aged 8.0–12.9 years that showed a negative association between the 20mSRT and cardiometabolic risk (as assessed by adiposity measures) and that the CRF cut-points from ROC analyses had a good discriminatory power for obesity [9]. In this study, the optimal suggested CRF cut-points for 8- to 12-year-olds were 39 mL·kg −1 ·min −1 and 41 mL·kg −1 ·min −1 for girls and boys, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our study extended the results of a recent study in 8740 Canadian children aged 8.0–12.9 years that showed a negative association between the 20mSRT and cardiometabolic risk (as assessed by adiposity measures) and that the CRF cut-points from ROC analyses had a good discriminatory power for obesity [9]. In this study, the optimal suggested CRF cut-points for 8- to 12-year-olds were 39 mL·kg −1 ·min −1 and 41 mL·kg −1 ·min −1 for girls and boys, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Although physical fitness and body adiposity may be correlated, they are not synonymous and indicate differing disease risks. In youth studies, several authors have shown that those with low levels of adiposity and low CRF are at a greater cardiovascular risk than high-adiposity adolescents with adequate CRF, independent of muscular fitness and body composition [9,10]. Recently, Silva et al [9] found that measurements using the 20-m shuttle run test in Canadian children aged 8–12 years were accurate to classify the sample by indicators of obesity in relation to the level of CRF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Silva et al published criterion-referenced cut-points for the mCAFT in a small sample of Brazilian youth aged 14-19 years (Silva et al 2016). More recently, criterion-referenced cut-points for CRF using the 20-m shuttle-run test were developed in a larger sample of Canadian children aged 8-12 years (Silva et al 2018). Comprehensive Canadian criterion-referenced cut-points for the mCAFT do not currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…Articles on criterion-referenced cut points for cardiorespiratory fitness in children, 17 sleep patterns, augmentation index, pulse wave velocity, insulin resistance, preschool children testing, cognition, arterial stiffness and so many others can be expected in the near future from the authors of this relevant and well-conducted paper.…”
mentioning
confidence: 99%